Analisis Pengendalian Internal Penerimaan Kas pada Rumah Sakit Umum Pusat Dr. Tadjuddin Chalid Makassar - Mutia Rizky Yunus Husain; Sitti Hajerah Hasyim; Mukhammad Idrus (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the internal control of cash receipts for general patient services at Dr. Central General Hospital. Tadjuddin Chalid Makassar. This research variable is internal control of cash receipts for general patient services. The population of this study were all documents relating to the internal control of cash receipts for general patient services at Dr. Central General Hospital. Tadjuddin Chalid Makassar. The sample for this study were informants related to the internal control of cash receipts for general patient services at Dr. Central General Hospital. Tadjuddin Chalid Makassar. The data collection techniques for this research are documentation and interviews. Data analysis was carried out using qualitative descriptive data analysis techniques. The results of this research indicate that the Internal Control System for Cash Receipts at Dr. Central General Hospital. Tadjuddin Chalid Makassar is in accordance with the Government's Internal Control System